PERAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DALAM PERKEMBANGAN GERAK DAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - Sartinah Sartinah (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
Athletic Subject Physical Education and Health is subject owning to have double role. Not even play a part in to develop aspect fitness of bodily, but also develop ability of motion and skilled of child social able to be made by stock in associating with positively with friends coeval him, in the environment of or in broader society environment. Elaborated Athletic Physical Education subject and Health, child can develop the hobby and talent at selected athletic branch so that can reach proud achievement and can bring the name of school fragrance, family, society and his nation. Besides, child also will grow and expand in an optimal fashion well-balanced but among/between physical and psychical, so that child will become router generation which with quality and made ready to become exponent for progress and feather in ones cap of nation later. Becoming duty of Atlitic Physical Education and Health teachers in Elementary School to realize the mentioned. Because if this matter succeed to be realized, will be able to prove in other teacher eye specially in Elementary School that Athletic Physical Education subject and Health is subject which is competent to be reckoned for the preparation of smart future generation, skilled, ad for godfearing august ethic and also to God Which Is Single The Most. Kata Kunci: Pendidikan Jasmani Olahraga dan Kesehatan, Perkembangan Gerak, Keterampilan Sosial